Is There a Need to Alter the Timing of Anti-Müllerian Hormone Measurement During the Menstrual Cycle? - Gorkem, Umit; Togrul, Cihan (Geburtshilfe und Frauenheilkunde, 2019)
Introduction There are numerous conflicting studies which have addressed the question whether the measurement of anti-Müllerian hormone (AMH) concentrations should be done at a certain time during the menstrual cycle. We aimed to investigate AMH fluctuations during the follicular and luteal phases of the menstrual cycle and to determine whether AMH variations, if present, might influence the clinical utility of ovarian reserve markers.Materials and Methods A total of 257 infertile women eligible for inclusion were categorized into three groups based on their total antral follicle count: 1. hypo-response group (< 7 follicles, n = 66), 2. normo-response group (7 – 19 follicles, n = 98), and 3. hyper-response group (> 19 follicles, n = 93).Results Mean follicular AMH levels were elevated compared to levels in the luteal phase in all response groups (p < 0.001). There were significant and strong positive correlations between follicular and luteal AMH levels in all response groups (Spearmanʼs r = 0.822, r = 0.836, and r = 0.899, respectively; p < 0.001 for all groups). Fisherʼs Z-test comparisons of these correlations in all response groups demonstrated that there was no statistically significant difference (Z = 0.277, Z = − 1.001, and Z = − 1.425, respectively; p < 0.001).Conclusion We found that serum AMH levels in the follicular phase were higher than those in the luteal phase in all three response groups. In current practice, fluctuations in serum AMH concentrations are not large enough to alter the timing of AMH measurements during the menstrual cycle. The issue is important for the assessment of ovarian reserve in infertile women with AMH levels near to the cut-off value.
Keywords: Anti-Müllerian hormone; AMH; fluctuation; ovarian reserve; variation; measurement